Young people’s political participation in the digital environment - S. A. Grishaeva; P. A. Shamaev (Цифровая социология)
Much of the time today's young people spend on the Internet, communicating with friends, receiving educational services, making online purchases. Such an important part of public life as political activity is no exception. The article is devoted to studying the opportunities and barriers of young people’s political participation in a digitalisation, to describing the different forms of this participation in the digital environment, and identifying the young people’s interest level in different forms of political participation online. The research paper carries out a content analysis of different ways of political participation: online flash mobs, Internet voting, platforms for collecting signatures, personal blogs, politically oriented communities, publications by popular bloggers. The content analysis data were supplemented by the questionnaire survey results of young people – active Internet users. The political participation modes were compared with each other in terms of their relevance to young people, including in the context of the using safety one mode or another. The research results provides an opportunity to designate the problem and significantly speed up the process of solving it, and will make it possible to considerably simplify the young people’s entry process into the political system through digital technologies.